UJI BAKTERIOLOGIS CABAI MERAH GILING (Capsicum annum L.) DARI BEBERAPA PASAR TRADISIONAL DI KOTA PADANG - Musliati, Desi; Fifendy, Mades; Periadnadi, Periadnadi (Pendidikan Biologi, 2013)
Abstract Chilli is one of commodity that never left by people. As the development of technology , instant production greatly favored by the people. One of that is minced chili that made from red chilli. From the market survey to minced red chilli tradisional traders at traditional market of Padang is that red chilli processing into minced chilli for public consumption still does not fulfill the requirements in terms of hygiene.This study aimed to test the bacteriological to minced red chlli ( Capsicum annum L.) from some traditional market in Padang City, which was conducted in June2013  at  the  Microbiology  Laboratory of  the  Department  of  Biology,  Andalas  University.This research was conducted with descriptive methods. Sample taking was picked up by purposive sampling which 2 sample were taken from each 5 traditional market in Padang, consist of Bandar Buat market, Gaung market, Lubuk Buaya market, Simpang Haru market, and Siteba market.Bacteriological testing is then performed with the steps :1.estimation test ( presumtive test ),2 . confirmation test ( confirmed test ) and 3 . completion test (completed test ) using the MPN method (Most Probable Number) by using a combination of 5:1:1. From the research, results obtained that minced red chili sample contain bacteria with the range number 43 x        cell/ml - 157 x         cell/ml. Minced red chili sample from five traditional market in Padang city have coliform bacteria MPN values range from 12.0 to 240.0 ml sample, and E. Coli bacteria from 7.5 to 240.0 cells / 100 ml sample. Concluded that minced red chili that sold in some traditional market in Padang city is generally not suitable for consumption because it contains E. coli > 3 colonies / g and coliform bacteria > 100 colonies / g.